2020
DOI: 10.1111/imr.12903
|View full text |Cite
|
Sign up to set email alerts
|

AIM2 in health and disease: Inflammasome and beyond

Abstract: Nucleic acid sensing is a critical mechanism by which the immune system monitors for pathogen invasion. A set of germline‐encoded innate immune receptors detect microbial DNA in various compartments of the cell, such as endosomes, the cytosol, and the nucleus. Sensing of microbial DNA through these receptors stimulates, in most cases, interferon regulatory factor‐dependent type I IFN synthesis followed by JAK/STAT‐dependent interferon‐stimulated gene expression. In contrast, the detection of DNA in the cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(101 citation statements)
references
References 155 publications
(202 reference statements)
0
91
0
1
Order By: Relevance
“…The cases of AIM2 and HLA-C are particularly interesting because each gene is represented by two differentially methylated CpG sites in our analyses, making it more likely that they contribute to the onset of the disorder. AIM2 is a member of the innate immune system that exerts vital activity during viral infections, and is responsible for the assembly of a macromolecular complex called the inflammasome that unleashes caspase-1 and triggers pro-inflammatory cytokines such as IL-1β and IL-18 [35] . HLA-C is another example of a candidate for mediating COVID-19 severity since specific HLA subtypes have been associated with susceptibility for many viral infections, including HIV, HBV, H1N1, HCV and HPV [36] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cases of AIM2 and HLA-C are particularly interesting because each gene is represented by two differentially methylated CpG sites in our analyses, making it more likely that they contribute to the onset of the disorder. AIM2 is a member of the innate immune system that exerts vital activity during viral infections, and is responsible for the assembly of a macromolecular complex called the inflammasome that unleashes caspase-1 and triggers pro-inflammatory cytokines such as IL-1β and IL-18 [35] . HLA-C is another example of a candidate for mediating COVID-19 severity since specific HLA subtypes have been associated with susceptibility for many viral infections, including HIV, HBV, H1N1, HCV and HPV [36] .…”
Section: Resultsmentioning
confidence: 99%
“…The AIM2 gene is expressed in the cellular cytosol and, upon detection of host-DNA released in the context of viral infections, initiates the assembly of the inflammasome complex, subsequent activation of the caspase-1 and a marked innate immune response involving release of cytokines IL-1β and IL-18. AIM2 cannot distinguish between viral DNA and self-DNA, so, whereas this lack of specificity provides a good defence against a wide spectrum of pathogens, the activation of AIM2 also affects host cells that produce exacerbated immune responses [35] . In this regard, viral infections of the lung associated with abnormal pulmonary inflammation, pneumonitis, fibrosis and respiratory tract sequelae have related AIM2 hyperactivity [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since ASC adaptor protein is present in other inflammasomes, such as AIM2 (Schroder and Tschopp, 2010 ), it is possible that other inflammasomes could also play a role in the age-associated inflammation and follicle depletion. Indeed, the AIM2 inflammasome senses host- and pathogen-associated cytosolic dsDNA, leading to caspase-1 activation and catalytic cleavage of IL-1β and IL-18 pre-forms (Kumari et al, 2020 ). A recent publication indicated that release of DNA after cumulative cell damage in aging cells leads to activation of cytosolic DNA sensors that trigger an inflammatory response (Lan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the role of AIM2 in cancer development is less clear. AIM2 has long been regarded as a tumor suppressor gene because reduced expression has been reported for colon, liver, breast, and liver cancers [ 10 , 35 ]. More recent studies have shown, however, that AIM2 is upregulated in squamous cell carcinoma and lung cancer [ 36 , 37 ].…”
Section: The Pyhin Protein Familymentioning
confidence: 99%
“…The early findings that PYHIN coding genes cluster within an IFN-inducible locus [ 17 , 40 ] and that the HIN domain allows DNA binding [ 14 ] suggested that PYHIN proteins might play a role in innate immunity. The role of AIM2 as an innate sensor of cytosolic dsDNA has been the topic of recent in-depth reviews [ 9 , 10 , 35 , 41 ]. In brief, recent data suggest that AIM2 forms small oligomers that fail to activate downstream signaling in the absence of dsDNA in the cytoplasm ( Figure 2 a) [ 42 ].…”
Section: Pyhin Proteins As Innate Dna Sensorsmentioning
confidence: 99%